Self organized nanostructures of amphiphilic block copolymers II - Müller, Axel H. E.; Borisov, Oleg; Aseyev, V. (Advances in Polymer Science, 2011)
Thomas Hellweg Block Copolymer Surfactant Mixtures in Aqueous Solution: Can we Achieve Size and Shape Control by Co-Micellization? Vladimir Aseyev Heikki Tenhu Françoise Winnik Non-ionic Thermoresponsive Polymers in Water Yun Yan Arie de Keizer Martien A. Cohen Stuart Nicolaas A. M. Besseling From Coordination Polymers to Hierarchical Self-Assembled Structures Ioan Botiz Helmut Schlaad Günter Reiter Processes of Ordered Structure Formation in Polypeptide Thin Film Solutions Katarzyna Kita-Tokarczyk Mathias Junginger Serena Belegrinou Andreas Taubert Amphiphilic Polymers at Interfaces.